Surge Arrester Monitoring Implementation at 33kV Distribution Overhead Line in Malaysia - Abdullah N.; Ariffin M.F.; Hatta N.M.; Nozlan M.F.; Mohamad A.; Osman M. (Institute of Electrical and Electronics Engineers Inc., 2024)
Aged and failed line surge arresters (LSA) would reduce the overvoltage protection for the equipment, leave equipment unprotection and shorten its lifetime. LSA failure can cause transient and nuisance tripping in the system reducing the overall work performance index (SAIDI) in a distribution network system. Pilot implementation of suitable technologies for LSA monitoring available in the market was conducted on a 33kV study line for 10 months since September 2020. The project has provided inputs for the development of a guideline document for the in-service LSA health conditions monitoring which is used as an operation & maintenance reference. The potential LSA monitoring system with IoT capability implemented in this project is to be considered for future deployment as part of SmartUtility 2025 initiatives in enhancing work management and increasing system reliability and efficiency in the Tenaga Nasional Berhad distribution network. A better understanding of the in-service LSA monitoring technology working principles and feasibility of wide implementation in the Distribution Network Medium Voltage overhead line network system has been achieved through this project. 2023 IEEE.